Special Themed Section on Emerging Findings From the Frontlines of Juvenile Justice Transformation - Walker, Sarah C. (Criminal justice and behavior, 2023)
In this special themed section, we desired to highlight findings in transformative areas of juvenile justice operations. Our initial goal was not to focus on ancillary treatment programs, probation programs, court processes, diversion, and/or leadership training. That is, we were interested in scholarly studies that examined fundamental transformations in system operations. We discovered that there was little academically oriented research that was being devoted to documenting, studying, and measuring the impact of these transformation, and that there are few efforts to advance our knowledge about both how to do transformation and the resulting impacts of these transformations. We were primarily interested in system change at the macro-level to help inform others about what transformation no the ground looks like, and how it affects the operations of a juvenile justice system.